2019
DOI: 10.1177/0898010119883760
|View full text |Cite
|
Sign up to set email alerts
|

Reintegration for Post-treatment Cancer Survivors: A Concept Analysis

Abstract: Background: Cancer survivors who have completed active treatments experience challenges in the survivorship phase of cancer care. Survivors transitioning through an illness experience negotiate former roles and relationships and reevaluate their self-identity. Reintegration of post-treatment cancer survivors has not been analyzed; however, nurses with a clear understanding of reintegration influence holistic care. Purpose: The goal of this artricle is to provide a theoretical definition of the concept of reint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Similarly, reintegration after cancer treatment, arguably the stakeholders' main priority outcome for future research, is a complex construct that would require multiple measures to assess in a holistic and meaningful way. Ore and Foli [28] recently published a concept analysis on reintegration post-cancer treatment that demonstrated the dynamic and evolving nature of this outcome, which involves a reorganization of roles and personal abilities to create a new normal and post-treatment identity. The authors provide some suggested tools to help assess this concept such as symptom scales as well as the Self-Perception and Relationships Tool [29] and the Reintegration to Normal Living Index [30].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, reintegration after cancer treatment, arguably the stakeholders' main priority outcome for future research, is a complex construct that would require multiple measures to assess in a holistic and meaningful way. Ore and Foli [28] recently published a concept analysis on reintegration post-cancer treatment that demonstrated the dynamic and evolving nature of this outcome, which involves a reorganization of roles and personal abilities to create a new normal and post-treatment identity. The authors provide some suggested tools to help assess this concept such as symptom scales as well as the Self-Perception and Relationships Tool [29] and the Reintegration to Normal Living Index [30].…”
Section: Discussionmentioning
confidence: 99%
“…Although measurement tools to assess the outcome are lacking, study authors cited examples, including the Reintegration to Normal Living Index. 19,20 Reintegration in cancer survivor literature is lacking, as sources have primarily focused on individual components related to reintegration, such as return to work for adults or return to school for childhood survivors. There are primary studies [21][22][23][24] and systematic reviews [25][26][27][28] on individual components that may fall within reintegration; for example, interventions addressing return to work, 21,25 exercise interventions for psychological improvement, 22,26 body image and sexual function interventions, 23,27 peer support groups, 24 and self-management regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Ore and Foli published a concept analysis on reintegration post-cancer treatment 19 . Reintegration is a distinct concept compared with related outcomes, such as quality of life, degree of well-being, post-traumatic growth, resilience, or rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations